Masques : revue des homosexualités. (Paris : Masques, 1979)
Fonds Suzan Daniel (FSD)
Periodiciteit: driemaandelijks. Doorlopende nummering.
Redactie: c/o Librairie Anima, 3 rue Ravignan, 75018 Paris ; vanaf (1981) 11: BP 126, 75863 Paris. Cedex 18
Frans
Periodiek